Inadequate Access to Potable Water Impacts Early Childhood Development in Low-Income Areas in Cape Town, South Africa - Caradee Y. Wright; Thandi Kapwata; Caylee Cook; Steven J. Howard; Hleliwe Makaula; Rebecca Merkley; Mbulelo Mshudulu; Nosibusiso Tshetu; Natasha Naidoo; Gaia Scerif; Catherine E. Draper (Ubiquity Press, 2023)
Background: Water and sanitation are vital to human health and well-being. While these factors have been studied in relation to heath, very little has been done to consider such environmental risk factors with child development. Here, we investigated possible relations between household water access/storage and early childhood development in four low-income settlements in the City of Cape Town, Western Cape province of South Africa. Our objectives were 1) to determine water access/storage practices in dwellings of children; 2) to assess early childhood development; and 3) and to understand the relationship between water access/storage practices in relation to early childhood development. Methods: We used a questionnaire to assess household water risk factors and the International Development and Early Learning Assessment (IDELA) tool to assess child early learning / cognitive, socio-emotional and motor development. Results: Mean age of the children (N=192) was 4 years and 55% were female. The mean IDELA score was 48% (range: 36% - 54%) where the higher the score, the better the child's development. Around 70% of households had a tap inside their dwelling and half said that they stored water with the largest percentage of storage containers (21%) being plastic/no lid. Child IDELA scores were lower for children living in households that did not have an indoor tap and for households who stored water. Conclusions: Given the risks associated with climate change and the already poor conditions many children face regarding water and sanitation, research is needed to further investigate these relations to provide evidence to support appropriate interventions and ensure healthy child development.